An electronic health record–based interoperable eReferral system to enhance smoking Quitline treatment in primary care. (15th May 2019) - Fiore, Michael; Adsit, Rob; Zehner, Mark; McCarthy, Danielle; Lundsten, Susan; Hartlaub, Paul; Mahr, Todd; Gorrilla, Allison; Skora, Amy; Baker, Timothy
Abstract: Objective: The study sought to determine whether interoperable, electronic health record–based referral (eReferral) produces higher rates of referral and connection to a state tobacco quitline than does fax-based referral, thus addressing low rates of smoking treatment delivery in health care. Materials and Methods: Twenty-three primary care clinics from 2 healthcare systems (A and B) in Wisconsin were randomized, unblinded, over 2016-2017, to 2 smoking treatment referral methods: paper-based fax-to-quit (system A =6, system B = 6) or electronic (eReferral; system A = 5, system B = 6). Both methods referred adult patients who smoked to the Wisconsin Tobacco Quitline. A total of 14 636 smokers were seen in the 2 systems (system A: 54.5% women, mean age 48.2 years; system B: 53.8% women, mean age 50.2 years). Results: Clinics with eReferral, vs fax-to-quit, referred a higher percentage of adult smokers to the quitline: system A clinic referral rate = 17.9% (95% confidence interval [CI], 17.2%-18.5%) vs 3.8% (95% CI, 3.5%-4.2%) ( P <  .001); system B clinic referral rate = 18.9% (95% CI, 18.3%-19.6%) vs 5.2% (95% CI, 4.9%-5.6%) ( P <  .001). Average rates of quitline connection were higher in eReferral than F2Q clinics: system A = 5.4% (95% CI, 5.0%-5.8%) vs 1.3% (95% CI, 1.1%-1.5%) ( P <  .001); system B = 5.3% (95% CI, 5.0%-5.7%) vs 2.0% (95% CI, 1.8%-2.2%) ( P <  .001). Discussion: Electronic health record–based eReferral provided an effective, closed-loop, interoperable means of referring patients who smoke to telephone quitline services, producing referral rates 3-4 times higher than the current standard of care (fax referral), including especially high rates of referral of underserved individuals. Conclusions: eReferral may help address the challenge of providing smokers with treatment for tobacco use during busy primary care visits. ClinicalTrials.gov; No. NCT02735382 .